Diagnostic and prognostic evaluation of novel biomarkers compared to ESC 0/1 h and 0/3 h algorithms in patients with suspected non-ST-elevation myocardial infarction - Yildirim, Mustafa; Salbach, Christian; Müller-Hennessen, Matthias; Frey, Norbert; Giannitsis, Evangelos (Journal of Clinical Medicine, 2025)
(1) Background: Prompt acute coronary syndrome (ACS) recognition remains challenging. This study evaluated the diagnostic and prognostic performance of novel biomarkers for non-ST-elevation myocardial infarction (NSTEMI). (2) Methods: Patients with suspected ACS presenting to Heidelberg University Hospital’s Emergency Department between August 2014 and February 2023 were analyzed. The biomarker panel included high-sensitivity cardiac troponin T (hs-cTnT), cardiac myosin-binding protein C (cMyBP-C), pro-B-type natriuretic peptide (proBNP), total N-terminal pro-B-type natriuretic peptide (t-NtproBNP), Angiotensin II (Ang2), Bone morphogenetic protein 10 (BMP10), Endothelial cell-specific molecule 1 (ESM1), fatty acid-binding protein 3 (FABP3), Fibroblast growth factor 23 (FGF23), Growth differentiation factor 15 (GDF15), and Copeptin. Negative predictive values (NPVs), sensitivities, and area under the curve (AUC) values were calculated for NSTEMI discrimination. Effectiveness and prognostic performance were assessed based on cardiovascular events at 30 days and 1 year. (3) Results: Of 1765 patients, 212 (12%) were diagnosed with NSTEMI. The European Society of Cardiology (ESC) 0/1 h and 0/3 h algorithms achieved sensitivities of 100% and 96.8%, NPVs of 100% and 99.3%, and effectiveness values of 54.8% and 66.0%. Hs-cTnT (AUC: 0.922) and cMyBP-C (AUC: 0.917) exhibited the highest diagnostic accuracy, followed by FABP3 (AUC: 0.759) and Copeptin (AUC: 0.624). Other biomarkers had lower performance (AUC: 0.516-0.617). At 1 year, event rates ranged from 0.0% to 3.4%, with the ESC algorithms demonstrating superior prognostic performance (0.8%, 2.4%). (4) Conclusions: The ESC 0/1 h and 0/3 h algorithms remain the most effective NSTEMI diagnostic strategies, balancing high sensitivity, prognostic reliability, and effectiveness. Among novel biomarkers, only cMyBP-C demonstrated comparable accuracy to hs-cTnT, supporting its potential as an adjunct to troponin assays.